Income Inequality Decomposition by Income Source and the Breakdown of Inequality Differences Between Two Population Subgroups - Jacques Silber; Yves Flückiger (Luxembourg Income Study (LIS), 1994)
This paper suggests a methodology to determine the precise role played by various income sources in the inequality of the distribution between male- and female-headed families and the overall income inequality in Switzerland.
Keywords: 330